2012
DOI: 10.1075/sic.9.3.04mar
|View full text |Cite
|
Sign up to set email alerts
|

On the relationship between L2 pronunciation and culture

Abstract: The purpose of this study is to determine the relationship between students' cultural sensitivity and changes in their pronunciation while abroad The relationship between L2 pronunciation in Spanish and cultural sensitivity is explored in the study-abroad context. A significant correlation is discovered between the students' score on the Inventory of Cross-cultural Sensitivity and improvements in the accuracy of their pronunciation as judged by a panel of native Spanish speakers. This study provides empirical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
8
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 23 publications
2
8
0
1
Order By: Relevance
“…Intercultural development prior to students' departure for their experiences abroad also predicted gains in their L2 skills. This finding corroborates evidence from other recent studies that have also uncovered a relationship between L2 acquisition and culture learning while abroad (Martinsen, 2010;Martinsen & Alvord, 2012;Vande Berg et al, 2009). This suggests that students' abilities to deal effectively with other cultures affects their L2 learning, at least in the study abroad context.…”
Section: Intercultural Sensitivitysupporting
confidence: 92%
“…Intercultural development prior to students' departure for their experiences abroad also predicted gains in their L2 skills. This finding corroborates evidence from other recent studies that have also uncovered a relationship between L2 acquisition and culture learning while abroad (Martinsen, 2010;Martinsen & Alvord, 2012;Vande Berg et al, 2009). This suggests that students' abilities to deal effectively with other cultures affects their L2 learning, at least in the study abroad context.…”
Section: Intercultural Sensitivitysupporting
confidence: 92%
“…The findings also supported the general concept of the effectiveness of attitude in language learning process as reported previously in many studies (Rukh, 2014;Martinsen & Alvord, 2012). The results of the study further confirmed Elliot's (1995) findings, where positive attitude was found to be the main variable in relation to language pronunciation, implying that students who were more concerned about their pronunciation, had more positive attitude towards target language and; therefore, were more successful in imitating correct pronunciation.…”
Section: Research Question 3: Testing the Correlation Between Attitudsupporting
confidence: 80%
“…Perhaps other individual differences were better predictors of learning than any of those collected in this study. Other individual difference factors not considered but potentially predictive of learning are phonological awareness (Venkatagiri & Levis, 2007), cross-cultural sensitivity (Martinsen & Alvord, 2012), and musical ability (Morgan, 2005), among others.…”
Section: Discussionmentioning
confidence: 99%